Features of the Diagnosis of Respiratory Diseases in Children Nowadays - K.D. Duka; A.O. Yefanova (Zaslavsky O.Yu., 2015)
Nowadays, respiratory diseases occupy a dominant position in the structure of morbidity in children, and clinic picture of various respiratory diseases has similar features. That's why the qualitative diagnosis of respiratory diseases in children is so important for choosing the right treatment. During the study, we have found that the diagnosis of acute respiratory diseases in surveyed children meets diagnostic criteria approved by clinical protocols. Diagnosis of viral infections should include clinical manifestations and paraclinical researches: detection of virus antigen and antibodies to the virus, and diagnosis of bacterial respiratory infections should be based on the determination of procalcitonin levels.